Current Perspectives on the Management of Reactive Attachment Disorder in Early Education - Bosmans G; Verschueren K; Cuyvers B; Minnis H (Psychology Research and Behavior Management, 2020)
Guy Bosmans,1 Karine Verschueren,2 Bien Cuyvers,1 Helen Minnis3 1Department of Clinical Psychology, Katholieke Universiteit Leuven, Leuven, Belgium; 2Department of School Psychology and Development in Context, Katholieke Universiteit Leuven, Leuven, Belgium; 3Institute of Health and Wellbeing, University of Glasgow, Glasgow, ScotlandCorrespondence: Guy BosmansPsychological Institute, Tiensestraat 102, Box 3720, Leuven 3000, BelgiumTel +32 16 32 61 87Email guy.bosmans@kuleuven.beAbstract: Children with Reactive Attachment Disorder (RAD) have special educational needs that are challenging for teachers in early education. In the current contribution, we will discuss a large body of research suggesting that stimulating these children’s attachment development is feasible for teachers and potentially a successful strategy to ensure that these children thrive better in the classroom and socially. The current overview discusses research and theory on RAD and RAD treatment and results in the formulation of specific recommendations for the successful management of children with RAD in the classroom.Keywords: attachment, treatment, teacher, dynamic model of the insecure cycle